Evropeizacija slovenske zunanje politike - Kajnč Lange, Sabina (Teorija in praksa, 2011)
The article analyses Slovenian foreign policy in relation to European foreign policy by using the concept of Europeanisation, It looks at the decade leading to Slovenia's accession to the European Union (EU) and at the first four years of its membership. After setting out the analytical framework for studying Europeanisation in foreign policy, the article presents in parallel both dimensions of Europeanisation (bottom-up and top-down) in Slovenian foreign policy. The article focuses on: (i) organisational structures (Ministry of Foreign Affairs); (ii) the major contours of fundamental foreign policy relations (Western Balkans); and (iii) some practices and principles (as well as values) which guided Slovenia's foreign policy during its accession period and in the first years of its membership in the EU. The article shows that both dimensions of Europeanisation are present in Slovenian foreign policy, although it was not until Slovenia held the presidency of the Council of the EU in the first half of 2008 that it actively co-operated in and co-shaped European foreign policy.
Keywords: Foreign policy; Zunanja politika; Europeanization; Evropeizacija; Slovenia; Slovenija; mednarodni odnosi